Analysis of the Japanese particle ni in sentences that express locative states - Rodríguez Bravo, Andrea (2021)
This article deals with the variation of the particle ni in sentences that refer to locative states in the Japanese language. The results of the analysis of the particles are presented: wa, ga, and no; as well as the alternation of use of the verbs arimasu and imasu. The corpus of the present work is divided into excessive and ineffective sentences, each one with its respective formalization following the proposal of Moreno Cabrera (2003). Finally, the postulated by Langacker (1987, as cited in Moreno, 2003) is demonstrated, who postulates that adjectives, adverbs and prepositions determine the relationship of timelessness and, although time is present, it is not relevant. In this way, the role of locativity is highlighted. In the analyzed sentences, it is shown that adverbs determine locative sentences.